Does relative age affect career length in North American professional sports? - Steingröver, C.; Wattie, N.; Baker, J.; Schorer, J. (Sports Medicine, 2016)
Background: Relative age effects (RAEs) typically favour older members within a cohort; however, research suggests that younger players may experience some long-term advantages, such as longer career length. The purposes of this study were to replicate previous findings on RAEs among National Hockey League (NHL) ice hockey players, National Basketball Association (NBA) basketball players and National Football League (NFL) football players and to investigate the influence of relative age on career length in all three sports. Methods: Using official archives, birthdates and number of games played were collected for players drafted into the NBA (N = 407), NFL (N = 2380) and NHL (N = 1028) from 1980 to 1989. We investigated the possibility that younger players might be able to maximize their career length by operationalizing career length as players` number of games played throughout their careers. Results: There was a clear RAE for the NHL, but effects were not significant for the NBA or NFL. Moreover, there was a significant difference in matches played between birth quartiles in the NHL favouring relatively younger players. There were no significant quartiles by career length effects in the NBA or NFL. Conclusions: The significant relationship between relative age and career length provides further support for relative age as an important constraint on expertise development in ice hockey but not basketball or football. Currently, the reason why relatively younger players have longer careers is not known. However, it may be worth exploring the influence of injury risk or the development of better playing skills.